Writing System Modulates the Association between Sensitivity to Acoustic Cues in Music and Reading Ability: Evidence from Chinese–English Bilingual Children - Zhang, Juan; Meng, Yaxuan; Wu, Chenggang; Zhou, Danny Q. (Frontiers in Psychology, 2017)
Music and language share many attributes and a large body of evidence showed that sensitivity to acoustic cues in music was positively related to language development and even subsequent reading acquisition. However, such association was mainly found in alphabetic languages. What remains unclear is whether sensitivity to acoustic cues in music is associated with reading in Chinese, a morphosyllabic language. The present study aimed to answer this question by measuring music (i.e., musical metric perception and pitch discrimination), language (i.e., phonological awareness, lexical tone sensitivity), and reading abilities (i.e., word recognition) among 54 third-grade Chinese-English bilingual children. After controlling for age and nonverbal intelligence, we found that both musical metric perception and pitch discrimination accounted for unique variance of Chinese phonological awareness while pitch discrimination rather than musical metric perception predicted Chinese lexical tone sensitivity. More importantly, neither musical metric perception nor pitch discrimination was associated with Chinese reading. As for English, musical metric perception and pitch discrimination were correlated with both English phonological awareness and English reading. Furthermore, sensitivity to acoustic cues in music was associated with English reading through the mediation of English phonological awareness. The current findings indicate that the association between sensitivity to acoustic cues in music and reading may be modulated by writing systems. In Chinese, the mapping between orthography and phonology is not as transparent as in alphabetic languages such as English. Thus, this opaque mapping may alter the auditory perceptual sensitivity in music to Chinese reading.